Are there distinct subtypes of developmental dyslexia? - Chalmpe, Maria; Vlachos, Filippos (Frontiers in Behavioral Neuroscience, 2025)
IntroductionThe aim of this study was to identify if children with dyslexia can be distinguished into discrete categories based on their domain deficits, indicating various neurocognitive subtypes of developmental dyslexia (DD).MethodsThe sample included 101 students in the 3rd, 4th, 5th, and 6th grades of primary school (mean age 11.15 years) with a diagnosis of dyslexia from a public center and Greek as their native language. The students underwent tests assessing a wide range of abilities, specifically phonological, memory, attention, processing speed abilities, motor, visual, and visual-motor skills.ResultsCluster analysis revealed that children with dyslexia can be divided into three subtypes. The first subtype includes children identified based on their performance in tasks evaluating the phonological abilities, memory, attention, processing speed, along with visual-motor and visual skills. The second subtype comprises children identified based on their performance in memory abilities, motor, and visual-motor skills. The third subtype includes children identified solely based on their performance in the motor skills domain.DiscussionIn conclusion, our findings suggest that school-aged children with DD can be categorized into different subtypes with distinct neurocognitive characteristics. Furthermore, the results indicate that most children with dyslexia experience difficulties in more than one cognitive, sensory or motor domains, supporting contemporary models regarding the existence of multiple neurocognitive deficits in DD.